Results Of Ranking Of Breeds From The World Collection Of The Silkworth From The World Collection Of Silkworth Research Institute Of Sericulture, Characterized By High Biological Indicators - Abdrimova Gulbahor Erimmatovna; Oripov Otabek Oripovich; Eltaeva Aigerim Azat Kizi (Zien Journals, 2024)
Breeds from the world collection of silkworms research institute of sericulture, sex-marked at the green stage and characterized by high biological indicators, can be used to create 100% pure hybrids.
Keywords: silkworm; breed; sex; marking